The utilization of birds at neolithic WF16, southern Jordan: Cut marks, body parts, and experimental skinning. (10th August 2021) - White, Judith; Khoury, Fares; Greet, Ben; Mithen, Steven
Abstract: WF16 is an early Neolithic settlement in southern Jordan with a large bird bone assemblage (Number of Identified Specimens [NISP] = 7808), representing 18 families. We explore how the birds were utilized by considering cut marks and body part representation for each of the families represented, also drawing on the experimental skinning of buzzards, the most common bird in the assemblage. We conclude that the bird bones accumulated from a mix of activities including the exploitation of a seasonally abundant supply of migratory birds for food; the acquisition of skins, feathers and talons for decorative, symbolic and practical purposes; and the trapping of wildfowl and gamebirds as a supplementary food source to large mammals.